Perlawanan Etnis Muslim Rohingya terhadap Kebijakan Diskriminatif Pemerintah Burma-Myanmar - Gulia Ichikaya Mitzy (Institute of International Studies, 2014)
This research aims to provide a description that the emergence of resistances which committed by Muslim Rohingya in Burma-Myanmar is a result of discriminatory policy. Where there are differences pattern of resistance which carried out during 64 years or two periods of the government, namely Military Junta and Democratic Transition era. This research was based on cases of discrimination against Muslim Rohingya in Burma-Myanmar. Cases about discrimination which Muslim Rohingya accepted could be the basis of their resistance. Their resistance is not just physical but also tended to be subjective. The pattern differences factor is signaled caused by the change in government or an era. Besides, the majority reported news showed about their suffering, not about what have they done responding the policy or discriminatory treatment against them.